Farm economic evaluation of raspberry production - Apáti, F. (International Journal of Horticultural Science, 2014)
Hungary was considered as one of the most significant raspberry producers in the 1980’ies. The acreage and the produced quantity, however, reflected a decreasing tendency during the past two decades: the 7 000 hectares existing in the year of 1990 reduced to 1 500 hectares, the current territory does not reach the 500 hectares. The annual yield is only 1 to 3 thousand tons. The level of domestic fresh consumption is very low, due to the fact that it is a relatively expensive fruit for Hungarian consumers. The requirement of the processing industry is satisfied by raspberries from mainly Polish and Serbian import. These two countries belong to the biggest raspberry producing countries in the world by producing raspberries of more than 50 thousand tons. Comparing to the Hungarian production costs and yields they are able to transport their products here at a very low price, consequently they hold the prices at a low level. The profitability of the domestic raspberry production is rather unfavourable, production often shows a deficit even in orchards of good standard; furthermore the lack of labour causes an extremely great difficulty, which is an important component of the decline of the production independently from cost conditions.